STUDY OF THE EFFECT OF PROCESS VARIABLES ON THE BENEFICIATION OF IRON ORE USING JIG AND SPIRAL CONCENTRATOR : REVIEW - LUTHFI, FADHIL
Iron is a metal that is widely used in everyday life. In iron ore, minerals that are often found are magnetite and hematite. The extraction process (smelting) cannot be carried out due to low iron content and the presence of other impurities so that the beneficiation process is required. The gravity concentration method is the most widely used beneficiation method besides magnetic concentration in processing iron ore. The gravity concentration method has a simple separation principle, low operating costs, and does not use chemical reagents as a separating medium. In this literature study, the effect of process variables on the resulting product was studied using a jig and spiral concentrator. The process variables is very important to be reviewed because it affects the grade and recovery of the elements produced and the process of separating valuable minerals from the impurities. In this literature study, the collection of literature sources was carried out with the keywords iron ore, gravity concentration, jig, and spiral concentrator. Literature sources that were not related to the research objectives were eliminated. Each literature source is analyzed and conclusions are drawn about the effect of process variables on the beneficiation of iron ore. The process variables reviewed in the jig are feed size, water flow velocity, and stroke length. The process variables examined in the spiral concentrator are feed size, feeding rate, and percentage of solids. The conclusions from the discussion of process variables in each literature are combined in order to obtain new conclusions that can answer the objectives of the study. The results of a literature study on the effect of process variables on the jig show that the finer the feed size, the lower the iron grade and lower the separation efficiency. The optimal size of the iron ore in the jig is obtained at sizes above 1 mm. The effect of water flow velocity shows that the increase the water flow velocity, the iron grade tends to increase and iron recovery will decrease. The effect of stroke length and pulse rate on the jig shows that the increase the value of the stroke length and pulse rate, the iron grade will increase but iron recovery will decrease. The effect of the feed size on the spiral concentrator shows that the finer the feed size, the iron grade tends to decrease and the iron recovery will decrease. The optimal size of the iron ore in the spiral concentrator is above 0.053 mm. The effect of the feeding rate on the spiral concentrator shows that the increasing the feeding rate, the iron grade tends to decrease and the iron recovery will increase. The effect of the percentage of solids in the spiral concentrator shows that as the percentage of solids increases, the iron garde will increase and the iron recovery will decrease. The optimal value of the percentage of solids is in the range of 25-30%.